2017
DOI: 10.1111/ctr.13028
|View full text |Cite
|
Sign up to set email alerts
|

Early clearance vs persistence of de novo donor‐specific antibodies following lung transplantation

Abstract: Early post-lung transplantation, dnDSA occurred in 1/4 of recipients, was associated with peri-transplant risk factors and resulted in decreased survival. Spontaneous clearance of dnDSA, seen in one-third of recipients, was associated with a lower risk of acute rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 22 publications
4
35
0
Order By: Relevance
“…Islam et al focused on early clearance and persistence of de novo DSA as well. They were able to show that patients with early clearance of DSA had significantly less acute rejections and better graft survival . Verleden et al recommended to distinguish between transient and persistent DSA .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Islam et al focused on early clearance and persistence of de novo DSA as well. They were able to show that patients with early clearance of DSA had significantly less acute rejections and better graft survival . Verleden et al recommended to distinguish between transient and persistent DSA .…”
Section: Discussionmentioning
confidence: 99%
“…DSA appears frequently after lung transplantation; however, the pathophysiological impact is still not completely understood . The majority of de novo DSAs appear early after lung transplantation, mostly in the first year after transplantation . In recent years, there was a growing interest in persistence as opposed to spontaneous clearance of de novo DSA .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the interaction between PGD and cardiopulmonary bypass (CPB), the results were presented before and after adjusting for CPB. Because of the risk of DQ‐DSA on adverse outcomes, we performed a subgroup analysis to identify risk factors for developing DQ‐DSA . Similar multivariable models were evaluated as described previously, for the development of DQ‐DSA.…”
Section: Methodsmentioning
confidence: 99%
“…These data underscore the role of humoral immune responses in lung allograft rejection. Previous studies have identified risk factors for the development of DSA including pretransplant allosensitization, retransplantation, the lung allocation score (LAS), and primary graft dysfunction (PGD) . The associations of LAS and PGD with DSA suggest that proinflammatory events early after transplantation increase the risk of DSA development.…”
Section: Introductionmentioning
confidence: 99%